Eksekusi Harta Waris di Pengadilan Agama - Khoirul Muhtarom (Fakultas Hukum Universitas Islam Jember, 2014)
Execution as an act committed by a court of law to the losing party in a case are the rules and procedures for the continuation of the proceedings. Therefore, the execution is nothing else than the continuous action of the whole process of civil law. Execution is a unity that is not separate from the implementation of procedural rules. Religious Courts as one of Indonesia's judiciary, which is one of handle kewenngannya inheritance disputes. The execution of the estate has been taken based on a procedural stages of execution as set forth in HIR and R.Bg. but in practice the real execution in the field of technical and juridical obstacles occur because of differences between the legal rules governing the execution of personal property with the needs of the practice.